Does Good Governance Matter? Kazakhstan’s Economic Growth and Worldwide Governance Indicators - Aikozha Absadykov (Department of Government Studies Universitas Muhammadiyah Makassar, 2020)
Good governance is generally believed to improve country’s economic performance. This paper studies the relationship between the World Bank’s Worldwide Governance Indicators (Voice and Accountability, Political Stability and Absence of Violence, Government Effectiveness, Regulatory Quality, Rule of Law, Control of Corruption) and economic growth in terms of GDP per capita in Kazakhstan. The findings of the research indicate that there is a significant positive relationship between good governance and economic performance of Kazakhstan. Specifically, results show that the Control of Corruption has the strongest impact on GDP per capita.